Penerapan Asas Pacta Sunt Servanda Pada Perjanjian Tidak Tertulis Terkait Bagi Hasil Perikanan - Mohamad Djovan Kurniawan Mokodompit; Muthia Cherawaty Thalib; Dolot Alhasni Bakung (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the application of the Pacta Sunt Servanda principle to unwritten agreements related to fisheries product sharing. The aim of this research is to find out how the Pacta Sunt Servanda Principle is applied to unwritten agreements and to find out what are the obstacles to the application of the Pacta Sunt Servanda Principle to unwritten agreements regarding fishery product sharing. This research uses a normative juridical type of research. By using several approaches, namely: legislation (statute approach), conceptual approach (conceptual approach).The results of this research show that the principle of pacta sunt servanda indeed requires parties to mutually fulfill their obligations in accordance with Article 1338 of the Civil Code. The agreement will be implemented if it meets the requirements in Article 1320 of the Civil Code and the parties mutually agree as per the meaning of Article 1313 of the Civil Code. When the agreement is ratified by the parties, the principle of pacta sunt servanda will apply. Apart from that, the results of this research also show that there are obstacles to the application of the principle of pacta sunt servanda in unwritten agreements regarding fishery product sharing, profit sharing agreements are general or not specific to a sector, so that we know about marine fisheries product sharing agreements as the author's research object. referring to law number 16 of 1964 concerning fishery product sharing agreements.